PARENTS' PERCEPTIONS OF SEX EDUCATION FOR CHILDREN IN PALUH MANIS VILLAGE, GEBANG DISTRICT, LANGKAT REGENCY - Novita Sari; Syarbaini Saleh; Yummy Jumiati Marsa (UNIVERSITAS PAKUAN, 2022)
This study aims to find out how parents view sex education in children in Paluh Manis Village, Gebang District, Langkat Regency. Sex education is important to give to children for the provision of their future life In qualitative research the research instrument is the person or human instrument, that is, the researcher himself. The informants used in this study, namely key informants, principal informants and auxiliary informants. The data collection techniques in this study, namely observation, interviews and documentation. Data analysis technique in this study using data validity techniques and data analysiss data. The results of the study found that sex education in children in the village can be said to be minimal. This is because some parents who live in the village still do not understand what is meant by sex education. The penelitian method used is a qualitative research method.